Colon cancer – etiology, symptoms and treatment - Review article - Ścirka, Natalia; Budny, Agnieszka (Journal of Education, Health and Sport, 2019)
Malignant neoplasm of the colon is the second in terms of cancer mortality in Poland in both sexes. Annually around 1.4 million cases are recognized in the world, and almost 700 thousand people die. There are many causes and risk factors for colon cancer include, among others; epithelial, genetic and dietary factors. Research Goal: Goal of this dissertation is a review of literature about colorectal cancer. Results: Despite performing screening, and the progress made in treating colon cancer patients, morbidity and mortality is still large and growing. It is therefore important to educate the public on the prevention of colon cancer, to combat bad eating habits and to promote healthy lifestyles.